Rabbitpox - Lyudmila F. Stovba; Aleksandr A. Petrov; Dеnis P. Belozerov; Oleg V. Chukhralia; Sergey A. Melnikov; Sergey V. Borisevich (Вестник войск РХБ защиты)
There is a danger that a natural smallpox virus may be reintroduced from the unknown spring or that a similar virus with the same pathogenic properties may appear or that somebody may create a synthetic copy of such a virus. That is why it is crucial to have a proper laboratory pattern that may imitate a natural smallpox disease and other human orthopoxviruses. A rabbitpox virus may provoke a grave and highly contagious disease in rabbits with a high death rate. The symptoms of this disease in rabbits is similar to symptoms of natural smallpox in humans. There have been no cases of rabbitpox in humans.Purpose of the study – To summarize data on research of a rabbitpox virus and to analyze the symptoms of this disease in rabbits that is similar to a natural pox virus in humans. This analysis may contribute to the development of new drugs against smallpox.Study base sources – English scientific papers available on the Internet.Method of the study – Analytical.Results and discussion. Rabbitpox was first detected in 1930 in lab. rabbits in Utrecht, the Netherlands, then in the USA, at Rockfeller University in New York. From 1941 the outbreaks of rabbitpox were registered in research institutes in Europe and in the USA. However, there were no cases of this disease in rabbits in the wildlife.  The analysis has demonstrated that  the pattern “a rabbit–a rabbitpox virus” has been quite successful in pre-clinical studies of protective efficiency of orthopoxvirus vaccines, monoclonal antibodies, mRNA-based drugs and chemotherapeutic agents (thiosemicarbazone, Cidofovir, tecovirimat, Brincidofovir, etc.) for different transmission modes including inhalative one. This pattern is also useful for evaluation of diagnostic sets, employed for orthopoxviruses detection.Conclusion. Pattern “a rabbit–a rabbitpox virus” is safe for humans and is promising for simulation of different pathological states when we conduct various medical and biological studies of orthopoxvirus infections. It also may be used to evaluate the efficiency of immunobiological drugs against smallpox, chemotherapeutic agents and diagnostic sets.